Assessing Islamic Banking Equity: A Synthesis of Financial Ratios and Economic Conditions - Mubarok, Faizul; Nurhasanah, Anggun; Fajarwati, Nabila Desinta; Salsabila, Shazkia (Program Studi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Kediri, 2024)
The success of companies in the banking sector is necessary for driving economic growth and state revenues. Their success is usually measured using their share prices which is a good index of their overall value. The objectives of this paper were to analyse the relationship between independent variables and share prices of Islamic Banking companies. The independent variables are the following financial ratios for indicators Return on Assets, Return on Equity, Debt to Equity Ratio, Debt to Asset Ratio, Inflation, interest rates and exchange rates. The study made use of the random effects data model to analyse the various Islamic Banking firms that are listed capital market, using data from 2020 to 2023. The results from the study were that Return on Assets, Return on Equity, Debt to Equity Ratio and Debt to Asset Ratio had a statistically significant impact on the share prices of the Islamic Banking Companies. However, Inflation, Interest, and exchange rates did not have a statistically significant effect on stock prices. The results of this analysis will be useful for stakeholders in the Islamic banking sector as they know the most critical factors in determining the market’s valuation of a companies performance and results to help guide strategies for the future.